2013
DOI: 10.1161/circulationaha.111.064337
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Pollution and the Cardiovascular System

Abstract: Figure.Odds ratio of ischemic stroke onset for US Environmental Protection Agency categories (good and moderate) of mean ambient fine particulate matter air pollution (PM 2.5 ) levels in the 24 hours preceding stroke onset. Error bars indicate 95% confidence interval. Reproduced from Wellenius et al 5 with permission from the publisher. The increased risk was greatest within 12 to 14 hours of exposure. Update, 2010 to 2012: Cardiac Arrhythmia, Arrhythmia Precursors, and PollutionEvidence continues to be mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 123 publications
0
60
0
4
Order By: Relevance
“…For stroke, the HR is approximately 2.0 for smoking, 1.5 for atrial fibrillation, and 1.4 for diabetes mellitus (34). These risk factors, however, are only present for subgroups of the population.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For stroke, the HR is approximately 2.0 for smoking, 1.5 for atrial fibrillation, and 1.4 for diabetes mellitus (34). These risk factors, however, are only present for subgroups of the population.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…The American Heart Association (AHA) has produced a comprehensive statement describing the marked effect of air pollution (1,34). The AHA recommends that practicing physicians should educate pa-…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…Several reviews of these studies, including 2 American Heart Association scientific statements, describe the scientific findings and conclude that air pollution poses a risk to heart health. [1][2][3][4] You can help protect your health and the health of your family, neighbors, and community from risk caused by air pollution, including the risk to your cardiovascular health. The Environmental Protection Agency (EPA), American Heart Association, American Stroke Association, and American College of Cardiology have published a concise leaflet on "Heart Disease, Stroke and Outdoor Air Pollution" that is available online (www.epa.gov/airnow/ heart_flyer-1-28-10-final.pdf).…”
mentioning
confidence: 99%
“…4 Especially if air conditioning is not available, very hot weather is dangerous for those with heart disease, the elderly, and persons e412 Circulation…”
mentioning
confidence: 99%
“…the association between air pollution and near-term risk of myocardial infarction remains controversial. Some studies have shown an association, while other studies have found either no association or an association only for selected pollutants 3,9,30 . In a recent meta-analysis the most important pollutant was PM 2.5 with an RR of 1.02 (95% CI, 1.01-1.02) for every 10 µg/m 3 increase, which is in line with our findings 9 .…”
Section: Discussionmentioning
confidence: 96%